Multimodal therapies: glucose oxidase-triggered tumor starvation-induced synergism with enhanced chemodynamic therapy and chemotherapy. (8th January 2020) - Cheng, Kaiwu; Ling, Chuxuan; Gu, Dihai; Gao, Zhiguo; Li, Yaojia; An, Peijing; Zhang, Yu; You, Chaoqun; Zhang, Rui; Sun, Baiwang
Abstract : A tumor microenvironment is distinct from normal tissue cells in characteristic physiochemical conditions, based on which we can design tumor-specific therapy modalities. Abstract : A tumor microenvironment is distinct from normal tissue cells in characteristic physiochemical conditions, based on which we can design tumor-specific therapy modalities. Herein, we introduce a concept of multimodal therapies, which integrates the characteristics of each therapy modality for efficient tumor therapy: tumor starvation-triggered synergism with enhanced chemodynamic therapy and activated chemotherapy. Fe3 O4 nanoparticles (Fenton reaction catalysts) and a hypoxic prodrug tirapazamine (TPZ) were loaded in mesoporous silica nanoparticles (MSN) and GOX was grafted onto its surface, which was designed and fabricated for sequential multimodal therapies. Logically, glucose oxidase (GOX) deprived tumor cells of nutrients (glucose and oxygen) for starvation therapy and tumorous abnormality amplifications (elevated acidity, exacerbated hypoxia, and increased H2 O2 ) were amplified by the GOX-driven oxidation reaction simultaneously. Specifically, elevated acidity could accelerate the release of iron ions and enhanced Fenton reaction efficiency. Associated with increased H2 O2, an elevated ROS level was detected, which enhanced the chemodynamic therapy. Exacerbated hypoxia activated the hypoxic prodrug TPZ for tumor-specific chemotherapy programmatically. Particularly, via integrating starvation therapy, enhanced chemodynamic therapy, and activated chemotherapy, the sequential multimodal therapies were specifically designed for the tumor microenvironment and achieved effective abnormality amplifications and high therapeutic efficacy.